SMEs in E-Commerce Market Structure - Arum Arupi Kusnindar; Ayi Ahadiat; Ainur Rosidah (Valid: Jurnal Ilmiah, 2023)
This article discusses the structure of the e_commerce market in Indonesia with the Industrial Organization approach using Porter's Five Forces. The results of research on the structure of Indonesia's digital market e-commerce tend to be a contestable market with low barriers to entry, products and services sold must have sufficiently strong substitutes and costs (initial and sunk costs) to set up similar companies are not too high. The internet increases competition and the government's role is needed to avoid too high a market concentration